2013
DOI: 10.1007/s00428-013-1422-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid oncocytic/chromophobe renal cell tumours do not display genomic features of chromophobe renal cell carcinomas

Abstract: Hybrid oncocytic/chromophobe tumours (HOCT) are renal tumours recently described displaying histological features of both renal oncocytoma (RO) and chromophobe renal cell carcinoma (ChRCC), raising the question of their precise signification in the RO/ChRCC group. This study aimed to describe clinicopathological features of so called HOCT and to characterise their genomic profile. Five hundred and eighty-three tumours belonging to the ChRCC/RO group were retrospectively reviewed. Twelve tumours that could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
3
31
1
Order By: Relevance
“…A histopathological differentiation of benign renal oncocytomas from malignant chRCC is still difficult, even using multiple immunohistochemistry markers (Ng et al, 2016). There are also case reports on rare hybrid tumors (Noguchi et al, 1995), including oncocytic content (Pote et al, 2013) and the rare genetic disorder Brit-Hogg-Dube (BHD) syndrome (Vera-Badillo et al, 2012), where the coexistence of renal oncocytomas and chRCC was shown. The defective mitochondriogenesis was named as a possible source of microvesicles in chromophobe renal cell carcinomas.…”
Section: Furthermore Endocytosis Was Reported To Suppress Cancer Celmentioning
confidence: 99%
“…A histopathological differentiation of benign renal oncocytomas from malignant chRCC is still difficult, even using multiple immunohistochemistry markers (Ng et al, 2016). There are also case reports on rare hybrid tumors (Noguchi et al, 1995), including oncocytic content (Pote et al, 2013) and the rare genetic disorder Brit-Hogg-Dube (BHD) syndrome (Vera-Badillo et al, 2012), where the coexistence of renal oncocytomas and chRCC was shown. The defective mitochondriogenesis was named as a possible source of microvesicles in chromophobe renal cell carcinomas.…”
Section: Furthermore Endocytosis Was Reported To Suppress Cancer Celmentioning
confidence: 99%
“…However, to our knowledge, HOCT metastatic behavior has never been confirmed, raising the assertion by some investigators that these hybrid tumors might be benign (30). Consistent with this possibility, Pote and colleagues recently concluded that HOCT is genetically more similar to renal oncocytoma than ChRCC and may therefore be a renal oncocytoma variant (31). Regardless, given its indolent clinical behavior and lack of known metastatic potential, the rare possibility of HOCT should not justify routine resection of tumors with renal oncocytoma diagnosis favored on biopsy, because HOCT too is appropriate for surveillance (49).…”
Section: Discussionmentioning
confidence: 99%
“…A prospectively maintained nephrectomy database was queried to identify all patients who underwent partial or radical nephrectomy for pathologically confirmed renal oncocytoma or ChRCC between August 2003 and December 2012. One patient with four hybrid renal oncocytoma-ChRCC tumors was excluded from analyses due to indeterminate malignant versus benign pathology (30,31). CD117 and CK7 immunostain results were obtained from pathology reports, and classified as positive for moderate-to-strong/diffuse membranous stain, or as negative for absent or weak/focal (<10%) stain (25).…”
Section: Retrospective Patient Cohortmentioning
confidence: 99%
“…Hybrid renal tumors are uncommon types of cancer containing areas of renal oncocytoma and areas of chromophobe cell kidney carcinoma, and are the focus of several studies [35].…”
Section: Atypical Oncocytic Tumormentioning
confidence: 99%